Conceptual Design and Finite Element Fatigue Life Analysis of a Poppet Valve Spring Compressor. (17th August 2020) - Simons, Anthony; Quartey, Gideon; Frimpong Asante, Nathaniel
Abstract : In the overhauling of the internal combustion engine, a lot of tools are used and among them is the poppet valve spring compressor. In Ghana, auto mechanics at the "way-side" garages make use of improvised tools, such as pipes, pliers, and push rods, for compressing valve springs. However, there are some challenges associated with the usage of these tools which include misplacement of cotters, injuries, and sometimes valve bends. In this work, a review of some of the existing designs of the improvised tools was considered. Also, a survey was conducted to seek the opinion of users (auto technicians and/or mechanics) of the tools. A design was made for spring compression by incorporating a magnet with a pull force of 679.78 N to take care of the removal of cotters during valve assembly dismantling. In this research, an efficient and user-friendly poppet valve spring compression tool with a total mass of 0.88 kg was designed. Finite element analysis (FEA) was performed on the upper and lower parts of the tool to examine its response due to the loads that act on it during operation. It was discovered from the analysis that the upper frame of the valve spring compressor experienced the highest von Mises stress of 59.77 MPa at the neck region, whilst the corresponding fatigue analysis showed a maximum fatigue life of 8.355 × 10 9 cycles.